Characterization of organic anion transporting polypeptide 1b2 knockout rats generated by CRISPR/Cas9: a novel model for drug transport and hyperbilirubinemia disease - Xinrun Ma; Xuyang Shang; Xuan Qin; Jian Lu; Mingyao Liu; Xin Wang (Elsevier, 2020)
Organic anion transporting polypeptide 1B1 and 1B3 (OATP1B1/3) as important uptake transporters play a fundamental role in the transportation of exogenous drugs and endogenous substances into cells. Rat OATP1B2, encoded by the Slco1b2 gene, is homologous to human OATP1B1/3. Although OATP1B1/3 is very important, few animal models can be used to study its properties. In this report, we successfully constructed the Slco1b2 knockout (KO) rat model via using the CRISPR/Cas9 technology for the first time. The novel rat model showed the absence of OATP1B2 protein expression, with no off-target effects as well as compensatory regulation of other transporters. Further pharmacokinetic study of pitavastatin, a typical substrate of OATP1B2, confirmed the OATP1B2 function was absent. Since bilirubin and bile acids are the substrates of OATP1B2, the contents of total bilirubin, direct bilirubin, indirect bilirubin, and total bile acids in serum are significantly higher in Slco1b2 KO rats than the data of wild-type rats. These results are consistent with the symptoms caused by the absence of OATP1B1/3 in Rotor syndrome. Therefore, this rat model is not only a powerful tool for the study of OATP1B2-mediated drug transportation, but also a good disease model to study hyperbilirubinemia-related diseases.